2016
DOI: 10.3390/met7010006
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study for the Welding of Dissimilar EN AW 6082 and EN AW 5083 Aluminum Alloys by Friction Stir Welding

Abstract: Abstract:The aim of this study is to investigate the effect of keeping constant the tool rotational speed to the welding speed ratio (υ ratio) on the mechanical properties of the dissimilar friction stir welding of EN AW6082-T6 and EN AW5083-H111. Two different pins shaped as triangular and pentagonal were associated with the constant υ ratio. From the tensile test results, it was found that the υ ratio does not create an evident change in the weld joint strength. The small cavity-and tunnel-type defects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…It is therefore recommended to use a cylindrical or a conical pin profile with various features in the dissimilar Al alloy joints for good material flow to produce sound joints. [18], with permission from SAGE, 2018; (d) AA5083-AA6082 [34], with permission from the authors; (e) AA5083-AA6351 [57], with permission from Springer, 2013.…”
Section: Tool Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore recommended to use a cylindrical or a conical pin profile with various features in the dissimilar Al alloy joints for good material flow to produce sound joints. [18], with permission from SAGE, 2018; (d) AA5083-AA6082 [34], with permission from the authors; (e) AA5083-AA6351 [57], with permission from Springer, 2013.…”
Section: Tool Geometrymentioning
confidence: 99%
“…Recently, a comprehensive EBSD investigation for the AA5083-AA2024 joint was reported by Niu et al [91], as shown in Figure 9. As it can be seen from the EBSD orientation maps (Figure 9 a-d), tilted and elongated grains in the TMAZ and fine grains d in the SZ developed due to dynamic [14], with permission from Springer, 2018; (b) AA5083-AA7075, reproduced from [16], with permission from Springer, 2018; (c) AA5083-AA6351, reproduced from [18], with permission from SAGE, 2018; (d) AA5083-AA6082 [34], with permission from the authors; (e) AA5083-AA6351 [57], with permission from Springer, 2013.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected samples include A7A5-2-8 with the best strength properties, samples A7A5-3-12, which was rejected from the strength tests due to a defect, and sample A7A5-1-4 with medium strength properties. Similarly, Kasman et al [ 27 ] conducted analyses of the constant ω/v ratio for connections of dissimilar alloys and obtained both correct and defective welds. The samples with the same HIR index have a different Heat Input Index (HI), which is 0.32 for the sample with the best parameters, with average values of 0.16, the piece disqualified from the tests 0.48.…”
Section: Discussionmentioning
confidence: 99%
“…This reduces the weight of the engine while increasing the corrosion resistance. The use of the material EN AW 5083 can also be found in shipbuilding or hydraulic lines in aircraft [14][15][16].…”
Section: Introductionmentioning
confidence: 99%